High deformation and delamination mechanisms explained through mesoscale and nanoscale phenomena in pearlitic steel wires - Brandaleze, Elena (2024)
Pearlitic steel wires subjected to severe cold drawing deformation exhibit a unique combination of high strength and excellent ductility, making them suitable for critical applications such as hanging bridge cables, crane cables and tire cord. Torsion tests up to rupture are commonly used in the industry for quality control purposes. A flat fracture surface is indicative of wire aptitude, while a delaminated surface suggests degradation of mechanical properties. This paper aims to expand the understanding of the structural evolution and deformation mechanisms that occur during wire drawing, as well as the origin of delamination problems. Different deformation and strengthening mechanisms are identified and discussed, applying different microscopy techniques (optical microscopy, scanning electron microscopy, electron backscatter diffraction), synchrotron diffraction and atom probe tomography. The information is correlated with the cementite stability on the structure studied at meso, nano, and atomic scale, reaching an understanding of the compositional evolution of cementite and ferrite even at the very lowest level. All the obtained information, including thermal analysis and thermodynamic simulation results, allow to identify the deformation mechanisms present during cold drawing and at the delamination process. In addition, the compositional evolution of cementite and ferrite is also clarified by atom probe tomography.